"A family like ours": Demographic variations in information seeking behavior and community participation among parents of individuals with autism spectrum disorder (ASD). Issue 1 (24th February 2016) - Gibson, Amelia; Kaplan, Samantha J.
ABSTRACT: We surveyed 906 parents of individuals with Autism/Autism Spectrum Disorder (ASD) about their information seeking experiences and preferred information sources. Our findings suggest that the most popular information sources are local doctors, therapists, national organization websites and local parent networks.